Assessment of Hydrogen's Climate Impact Is Affected by Model OH Biases - L. H. Yang; D. J. Jacob; H. Lin; R. Dang; K. H. Bates; J. D. East; K. R. Travis; D. C. Pendergrass; L. T. Murray (Geophysical Research Letters)
Abstract Hydrogen fuel can help decarbonize the economy, but hydrogen leakage has indirect climate consequences. Atmospheric oxidation of hydrogen by hydroxyl radicals (OH) increases methane, ozone, and stratospheric water vapor concentrations. Current global 3‐D atmospheric chemistry models estimate a global warming potential for hydrogen of 12 ± 3 over a 100‐year horizon (GWP‐100), but the models overestimate global OH concentrations and underestimate OH reactivity (OHR). These OH biases cause overestimates of the responses of methane and ozone to hydrogen. Here, we compare the hydrogen GWP‐100 calculated from the standard GEOS‐Chem model and from a modified version where OH and OHR biases are corrected with missing organic emissions and a terminal OH sink over continents. The hydrogen GWP‐100 from the standard GEOS‐Chem model agrees with previous studies, but the modified version is 20% lower. Better understanding of the factors controlling global OH concentrations and OHR is needed to refine hydrogen GWP estimates.